The Role of Global Leadership in Driving Success in a Global Marketplace - Syarifuddin, Syarifuddin; A. Sobandi, A. Sobandi; Ahman, Eeng (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study explores the critical influence of global leadership on achieving organizational success within complex international markets. With globalization advancing, leaders face the challenge of managing cultural diversity, regulatory differences, and shifting market conditions. The research identifies key competencies for global leaders, including cultural intelligence, strategic foresight, adaptability, and ethical decision-making, which are essential for efficient cross-border management. Employing a qualitative approach, this study synthesizes insights from an extensive academic literature review, examining how these competencies impact organizational metrics such as market share, customer satisfaction, and employee engagement. Thematic analysis reveals that leaders with adaptability and strategic insight are better equipped to address technological innovations, regulatory changes, and socio-political issues. The conclusions emphasize the importance of developing leadership frameworks that support these competencies to bolster organizational resilience and competitive advantage globally. This study enriches the literature by linking global leadership competencies to quantifiable performance metrics and offering a foundational model for nurturing effective leadership in a swiftly transforming international landscape.Keywords: Global Leadership, Organisational Resilience, Leader Competencies, International Markets, Competitive Strategy